Management Coaching Teachers At Sdn Inpres Komba And Sdn Inpres Kemiri Sentani Jayapura Regency - Novita Riana Pararem; Tina Rahmawati (Didaktika: Jurnal Kependidikan, 2025)
Abstract Method. Qualitative research with a case study design explores teacher training strategies at SDN Inpres Komba and SDN Inpres Kemiri Sentani, Jayapura Regency, to improve teaching quality and teacher professional development. The population was teachers and teaching staff, with a purposive sample of 15-20 teachers with varying degrees of experience in training, supervision, and support. Data were collected through semi-structured interviews and focus group discussions (FGDs) to explore perceptions of new teacher orientation, academic support, and community engagement. Analysis using Voyant Tools (https://voyant-tools.org/) to identify thematic patterns from transcripts, with triangulation of principal and administrator perspectives, as well as ethics of written consent and confidentiality of identity. Results.Teachers responded positively to orientations that facilitated adaptations to teaching, local curricula, and remote challenges. Training support, resource access, and regular supervision fostered professional success, while community engagement fostered ownership, retention, and motivation. Voyant Tools revealed a dominant pattern of "teacher coaching," with recommendations for management, planning, and evaluation at SDN Komba and a competency-focused, evaluation cycle at SDN Kemiri. Discussion.Findings highlight a holistic contextual approach, principal-school collaboration, and theoretical-practical training for multicultural classroom needs. Triangulation addresses Jayapura logistics, continuous evaluation enhances optimal learning through stakeholder support. Conclusion: Voyant's integrated training strategy and analysis effectively improve teacher professionalism in remote Papua. Recommendations: community workshops and regular digital evaluations to ensure the sustainability of national education quality.